Perception and production of English fricatives by Hausa speakers / Alhaji Maiunguwa - Maiunguwa, Alhaji (2015)
The present study investigates the production and perception of the English fricatives /v/, /θ/ and /ð/ in initial and final positions at the words level by the Hausa ESL learners. Five masters’ students from the University of Malaya participated in the study. The objectives of the research were to investigate and identify the difficulties faced by Nigerian Hausa speakers of English in the production and perception of fricative sounds of English, and to study the relationship between the perception and production of second language sounds. The data were collected through two types of tests consisting of perception and production tests. The perception tests comprised three tasks; Identification, AX discrimination and 3 Alternative Forced Choice (3AFC) discrimination tasks. The analyses involved descriptive statistics. The results of the perception tests showed that most of the respondents were able to differentiate English labio-dental fricative and dental fricatives from voiced bilabial stop and alveolar stops accurately. The identification test results showed that the respondents could identify English /v/, /θ/ and /ð/ quite easily as the accuracy of all the respondents is 90%. It is shown in the AX discrimination and a 3AFC discrimination tests that the respondents could discriminate the English fricatives /v/, /θ/ and /ð/ quite well. In the production test, the results of the study showed that the position of the /v/, /θ/ and /ð/ sounds play an important role in their pronunciation. The findings revealed that the pronunciation of /v/, /θ/ and /ð/ in word-final position was more problematic than in word-initial position. The results confirm the correspondence between the production and perception of sounds. The respondents who obtained better scores in the perception tests also had relatively better scores in the production test. Therefore, the Speech Learning Model by Flege (1995) about the correspondence between perception and production of L2 phonemes is verified.